Solving the Puzzle of Recruitment and Retention—Strategies for Building a Robust Clinical and Translational Research Workforce - Nearing, Kathryn A. (Clin Transl Sci, 2015)
This paper is the first in a five‐part series on the clinical and translational science educational pipeline and presents strategies to support recruitment and retention to create diverse pathways into clinical and translational research (CTR). The strategies address multiple levels or contexts of persistence decisions and include: (1) creating a seamless pipeline by forming strategic partnerships to achieve continuity of support for scholars and collective impact; (2) providing meaningful research opportunities to support identity formation as a scientist and sustain motivation to pursue and persist in CTR careers; (3) fostering an environment for effective mentorship and peer support to promote academic and social integration; (4) advocating for institutional policies to alleviate environmental pull factors; and, (5) supporting program evaluation—particularly, the examination of longitudinal outcomes. By combining institutional policies that promote a culture and climate for diversity with quality, evidence‐based programs and integrated networks of support, we can create the environment necessary for diverse scholars to progress successfully and efficiently through the pipeline to achieve National Institutes of Health's vision of a robust CTR workforce.